2012
DOI: 10.1016/j.bbamem.2011.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Biophysics of α-synuclein membrane interactions

Abstract: Membrane proteins participate in nearly all cellular processes; however, because of experimental limitations, their characterization lags far behind that of soluble proteins. Peripheral membrane proteins are particularly challenging to study because of their inherent propensity to adopt multiple and/or transient conformations in solution and upon membrane association. In this review, we summarize useful biophysical techniques for the study of peripheral membrane proteins and their application in the characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
208
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(219 citation statements)
references
References 166 publications
(217 reference statements)
8
208
0
3
Order By: Relevance
“…The high affinity of α-synuclein for anionic lipids has been reconciled with the polarized nature of the protein. 50 The N-terminal half is positively charged (+2 at pH 7 and +4 at pH 5.5), and the C-terminal half is negatively charged (−11 at both pH values). A series of repeats in the Nterminal half are arranged so that, if this part folds into an α-helix upon membrane association, the helix has one polar ( Figure 9B) and one hydrophobic ( Figure 9C) side with lysine residues flanking the borders between them.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high affinity of α-synuclein for anionic lipids has been reconciled with the polarized nature of the protein. 50 The N-terminal half is positively charged (+2 at pH 7 and +4 at pH 5.5), and the C-terminal half is negatively charged (−11 at both pH values). A series of repeats in the Nterminal half are arranged so that, if this part folds into an α-helix upon membrane association, the helix has one polar ( Figure 9B) and one hydrophobic ( Figure 9C) side with lysine residues flanking the borders between them.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It has been suggested that the insertion of α-synuclein into the membrane can be facilitated by increasing the available area per phospholipid headgroup in the interface. 50 An increase in lipid headgroup area implies greater exposure of the hydrocarbon region in the bilayer. 51 To investigate this aspect, an additional experiment was conducted using a 7:3 DOPC/DOPS bilayer.…”
Section: Acs Chemical Neurosciencementioning
confidence: 99%
“…aSyn is known to interact with a variety of proteins and small molecules, such as tyrosine hydroxylase and tau, metal ions, and lipids (36 -40). The N-terminal and central NAC domains of aSyn interact with lipids in cellular membranes and with some proteins (41)(42)(43)(44), whereas the C-terminal domain was shown to bind metal ions (38). aSyn interactions with proteins, such as synphilin-1 (45) and tubulin (46), small molecules, and macromolecules, such as dopamine (47), polysaccharides (48), and metal ions (11) can enhance aggregation of aSyn.…”
Section: Discussionmentioning
confidence: 99%
“…The protein exists in a multitude of conformations that likely dictates the physiological function of α-syn (2-6). Upon membrane association, α-syn adopts an α-helical structure (7), whereas in solution, the protein is disordered (3,6,8). Elucidation of molecular mechanisms underlying the transformation of α-syn to a disease-associated species is still the subject of intense research.…”
Section: Protein-lipid Interactionsmentioning
confidence: 99%